Improvement of machining accuracy for 3D surface machining with CNC lathe - Keigo TAKASUGI; Yoshitaka MORIMOTO; Yoshiyuki KANEKO; Naohiko SUZUKI; Naoki ASAKAWA (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2018)
The present paper describes a new non-axisymmetric curved surface turning (NACS-Turning) method. Fast tool servo (FTS) technology has been widely researched and developed. However, the movable range of the FTS is limited to a few millimeters owing to its mechanism. Therefore, in the present study, we describe the development of a new NACS-Turning method that can realize long stroke and high bandwidth in the cutting direction (X-axis) of the turning tool by using a linear motor. We confirmed that NACS-Turning could machine a non-axisymmetric workpiece while the X-axis slide was synchronized at an acceleration of 4.5 g with a spindle rotation of 750 min-1. However, in this machining method, the machining accuracy deteriorates depending on the acceleration and cutting reaction force of the X-axis slide. In particular, excess from the designed allowable acceleration threatens to cause a serious machining error. Therefore, the present paper describes the possibility of machining considering the acceleration and improvement of machining accuracy in NACS-Turning. We examine the relationships between machining parameters and the accelerations as well as the tool path generation method considering these relationships. Moreover, machining accuracy is improved by on-machine measurement. We constructed a system whereby a re-machining tool path is generated by measuring the profile of the machined workpiece and feeding the measurement results back to the CAM. As a result, we obtained a theorem for the possibility of machining via NACS-Turning and confirmed the improvement in accuracy.